John Nils Almgren (1930–2021): An Outstanding Figure in Australian Telecommunications Manufacturing, and in Philanthropy - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2022)
John Nils Almgren AM (20 June 1930 to 24 December 2021) was renowned in the Australian telecommunications industry for his success, together with his wife Yvonne, in building a major Australian manufacturing company, J. N. Almgren Pty Ltd, starting from scratch in 1960. JNA began as a custom-designer of small electromechanical subsystems for the PMG and State electricity utilities, but later developed successful electronic products for public and private data networks for large corporations. The company was floated on the ASX in 1992 as JNA Telecommunications Ltd. It operated internationally until bought by the US company Lucent Technologies in 1998. John and Yvonne became significant philanthropists, often declining any publicity for their generous donations.